Triglyceride-glucose index, low-density lipoprotein levels, and cardiovascular outcomes in chronic stable cardiovascular disease: results from the ONTARGET and TRANSCEND trials - Haring, Bernhard; Schumacher, Helmut; Mancia, Giuseppe; Teo, Koon K.; Lonn, Eva M.; Mahfoud, Felix; Schmieder, Roland; Mann, Johannes F.E.; Sliwa, Karen; Yusuf, Salim; Böhm, Michael (European Journal of Preventive Cardiology, 2024)
Aims The triglyceride-glucose index (TyG) has been proposed as an alternative to insulin resistance and as a predictor of cardiovascular outcomes. Little is known on its role in chronic stable cardiovascular disease and its predictive power at controlled low density lipoprotein (LDL) levels. ............................................................................................................................................................................................ Methods Our study population consisted of 29 960 participants in the ONTARGET and TRANSCEND trials that enrolled patients and results with known atherosclerotic disease. Triglycerides and glucose were measured at baseline. TyG was calculated as the logarithmized product of fasting triglycerides and glucose divided by 2. The primary endpoint of both trials was a composite of cardiovascular death, myocardial infarction, stroke, or hospitalization for heart failure. The secondary endpoint was all-cause death and the components of the primary endpoint. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CI) with extensive covariate adjustment for demographic, medical history, and lifestyle factors. During a mean follow-up of 4.3 years, 4895 primary endpoints and 3571 all-cause deaths occurred. In fully adjusted models, individuals in the highest compared to the lowest quartile of the TyG index were at higher risk for the primary endpoint (HR 1.14; 95% CI 1.05–1.25) and for myocardial infarction (HR 1.30; 95% CI 1.11–1.53). A higher TyG index did not associate with the primary endpoint in individuals with LDL levels < 100 mg/dL. ............................................................................................................................................................................................ Conclusion A higher TyG index is associated with a modestly increased cardiovascular risk in chronic stable cardiovascular disease. This association is largely attenuated when LDL levels are controlled. ............................................................................................................................................................................................ Registration www.clinicaltrials.gov: NCT00153101 - Lay summary• The association of triglyceride-glucose index (TyG) with cardiovascular disease in chronic stable cardiovascular disease and its predictive power at controlled low density lipoprotein (LDL) levels is unclear. Using a study population of 29 960 participants with chronic stable cardiovascular disease, we found that higher TyG levels were associated with a modestly increased risk for incident cardiovascular events and low LDL levels largely attenuated the association of TyG with cardiovascular risk.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Cardiovascular disease; Mortality; Myocardial infarction; Triglyceride-glucose index